Comparison of some properties of Cu(II) 2,3- , 3,5- and 2,6-dimethoxybenzoates - Ferenc, Wieslawa; Walków-Dziewulska, Agnieszka; Sarzyński, Jan; Paszkowska, Barbara (Eclética Química, 2006)
The physico-chemical properties and thermal stability in air of Cu(II) 2,3- , 3,5- and 2,6-dimethoxybenzoates were compared and the influence of the position of –OCH 3 substituent on their thermal stability was investigated. The complexes are crystalline, hydrated salts with blue colour. The carboxylate ion is a bidentate chelating or bridging group. The thermal stability of analysed Cu(II) dimethoxybenzoates was studied in the temperature range of 293-1173 K. The positions of methoxy-groups in benzene ring influence the thermal properties of studied complexes. Their different thermal properties are markedly connected with the various influence of inductive, mesomeric and steric effects of –OCH 3 substituent on the electron density in benzene ring. The magnetic susceptibilities of the complexes were measured over the range of 76-300 K and the magnetic moments were calculated. The results show that they form dimers.